Numerical Simulation of Designing a Braking System by Comparing Pressure in Minibus Type Vehicle - Naufal Aflah Hibatullah; Adri Maldi Subardjah (Universitas Negeri Padang, 2022)
The braking system is crucial in maintaining the vehicle's safety to avoid fatality. However, designing a vehicle braking system can take significant time and energy. Hence, a method to design a braking system that requires less time and energy is necessary. The vehicle specifications will affect the braking design process in designing a braking system. In addition, the existing government regulations limit the braking capacity that must be achieved during the braking process. These two things become the limitations in designing an optimal braking system. The design process is carried out by determining the required pressure for the braking process and the pressure generated during the braking process. The generated pressure must exceed the required pressure for the braking system design to work appropriately. The conditions mentioned earlier can be achieved by iterating and selecting the standard component. A case study in the form of braking system design has been carried out where the braking system can generate a pressure of 4.14 MPa and requires a pressure of 3.13 MPa and 2.34 MPa at the front and rear caliper on a vehicle weighing 78.48 kN to decelerate 5 ms-2 as required in Indonesia government regulation. A comparison is made with other methods proposed by other researchers to ensure the proposed method can be applied to various conditions. The comparison results show that the proposed method can be applied to various conditions. Moreover, the proposed method can minimize the difference in pressure between the generated and the required pressure to avoid overdesign.